Assessment of the ease of insertion, retention rate, ease of removal and pig behaviour to a novel intravaginal insert for pigs - Jong, Kwang Yan (2016)
Reproduction is an important aspect of the swine livestock industry. It is one of the parameters that decides the amount of pigs that can be sold by pig farms. As Malaysia has a significant swine industry, having an effective reproduction is essential to the pig producers. This study evaluates the use of novel progesterone loaded intravaginal inserts to achieve oestrus synchronisation in gilts. It involves a model pig farm located in Bidor, Perak. Six gilts aged 8-months-old were used in this study. They were divided into three categories which were – short length size with small base (SS) and large base (SL), medium wing size with small base (MS) and large base (ML), and long length size with small base (LS) and large base (LL). The ease of insertion and removal of the device, the retention rate and pig behaviour were recorded. Devices SL and LL were not successfully inserted due to the large base. Device LS was removed 5 days after insertion as it caused discomfort. Devices SS, MS and ML were successfully removed on day 13th. In conclusion, the device achieved its aim of oestrus synchronisation but requires further studies to determine the appropriate materials and size.